SEISMIC MAPPING FOR TELECOMMUNICATION TOWERS IN MALAYSIA (Malaysian Journal of Civil Engineering, 2018)
Natural disaster like earthquake can affect the telecommunication facilities seriously. Although Malaysia is generally spared from major seismic activities, earthquakes events in neighboring countries can be felt locally. This has raised a major concern whether the existing structures being able to withstand earthquake effects in future. A proper management of telecommunication structures will allow transmission of news is not affected during the disaster strikes. Using the existing Peak Ground Acceleration (PGA) map, a seismic map locating all telecommunication towers in the country was developed. The outcome will aid in the subsequent part of the study and will also enable the researcher to identify the location of the most critical towers in the various seismic zones that may have great impact upon exposure from earthquakes events. It will also aid in defining priorities and establish programs to apply available resources for tower maintenance purposes nationwide. The necessary steps and mitigation action also can be taken to assists the relevant authority in making preparation from an emergency-management and hazard-preparedness perspective considering earthquake effects in Malaysia